2020
DOI: 10.1007/s11540-020-09451-3
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Photosynthetic Parameters and Drought-Induced Tuber Yield Decrease in Katahdin-Derived Potato Cultivars

Abstract: Potato (Solanum tuberosum L.) is considered a drought-sensitive crop species, although cultivar-dependent differences in tolerance have been described. The extent of drought-induced tuber yield decreases is considered the main criterion for potato tolerance to drought. In this study, eighteen closely related potato cultivars were subjected to drought stress, and among them, two groups with contrasting drought tolerance phenotypes were distinguished (tolerant: Sebago, Katahdin and Cayuga; susceptible: Sequoia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…However, the reduction in the rates of photosynthesis was similar in all genotypes, regardless of their differential tolerance ability to drought. Therefore, unlike previous findings (Plich et al, 2020 ), our current study suggests that the ability of the potato genotypes, Bannock Russet and Nipigon, to tolerate drought stress is not associated with the maintenance of photosynthesis under drought as compared with sensitive genotypes. Future research needs to confirm whether the differential ability of potato genotypes to maintain tuber yield under drought is due to the differences in the carbohydrate translocation to the stolon.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the reduction in the rates of photosynthesis was similar in all genotypes, regardless of their differential tolerance ability to drought. Therefore, unlike previous findings (Plich et al, 2020 ), our current study suggests that the ability of the potato genotypes, Bannock Russet and Nipigon, to tolerate drought stress is not associated with the maintenance of photosynthesis under drought as compared with sensitive genotypes. Future research needs to confirm whether the differential ability of potato genotypes to maintain tuber yield under drought is due to the differences in the carbohydrate translocation to the stolon.…”
Section: Discussioncontrasting
confidence: 99%
“…Drought stress substantially reduced A in all genotypes, such that A was ~2.4–5.6 μmol/m 2 /s among the genotypes under drought ( Table 2 ). This precludes the previous notion that the ability of potato plants to tolerate drought and thus maintain tuber yield is associated with their capacity to maintain higher A under drought (Plich et al, 2020 ). In vivo Chl a fluorescence was monitored in combination with the CO 2 gas exchange to estimate (1) the maximum photochemical efficiency of PSII in the dark-adapted state ( F v / F m ), a measure of plant stress condition, (2) the photosynthetic ETRs through PSII, and (3) NPQ, the capacity to dissipate energy as heat.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In many agricultural areas, recent climate change is a serious threat and drought is a major limitation for tree growth and productivity worldwide. Previous research demonstrated that drought stress inhibits vegetative growth (Tsuchida et al 2011, Blanco et al 2020) and reduces fruit yield and quality (Pérez-Pérez et al 2008). Under drought stress conditions, many morphological and physiological processes in plants, such as water content, membrane stability, and photosynthetic activity, are negatively affected (Abid et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The potato is a water-deficit sensitive crop species, and water deficits reduce photosynthetic capacity and yield, which are mainly caused by stomatal limitation and nonstomatal limitations related to damage to the photosynthetic apparatus [14,56,57]. The results in Table 1 indicate a decrease in the tuber fresh weight per plant under water deficit conditions, which was accompanied by a reduction in F v /F m and RWC.…”
Section: Discussionmentioning
confidence: 99%